The price is right: Updating of inflation expectations in a randomized price information experiment - Olivier Armantier; Scott Nelson; Giorgio Topa; Wilbert van der Klaauw; Basit Zafar (Federal Reserve Bank of New York, 2012)
Understanding the formation of consumer inflation expectations is considered crucial for managing monetary policy. This paper investigates how consumers form and update their inflation expectations using a unique information experiment embedded in a survey. We first elicit respondents' expectations for future inflation either in their own consumption basket or for the economy overall. We then randomly provide a subset of respondents with infl ation-relevant information: either past-year food price inflation, or a median professional forecast of next-year overall inflation. Finally, inflation expectations are re-elicited from all respondents. This design creates unique panel data that allow us to identify the effects of new information on respondents' inflation expectations. We find that respondents revise their inflation expectations in response to information, and do so meaningfully: revisions are proportional to the strength of the information signal, and inversely proportional to the precision of prior inflation expectations. We also find systematic differences in updating across demographic groups and by question wording, underscoring how different types of information may be more or less relevant for different groups, and how the observed impact of information may depend on methods used to elicit infl ation expectations.
Keywords: C81; D80; E31; 330; inflation expectations; information; heterogeneous expectations; updating